2011
DOI: 10.1109/tasl.2010.2076806
|View full text |Cite
|
Sign up to set email alerts
|

Phase Minimization for Glottal Model Estimation

Abstract: Abstract-In glottal source analysis, the phase minimization criterion has already been proposed to detect excitation instants. As shown in this article, this criterion can also be used to estimate the shape parameter of a glottal model (ex. LiljencrantsFant model) and not only its time position. Additionally, we show that the shape parameter can be estimated independently of the glottal model position. The reliability of the proposed methods is evaluated with synthetic signals and compared to that of the IAIF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Nevertheless, using PD, it has been shown that this assumption allows to extract glottal source information which is almost independent of the vocal tract filter [40]. Indeed, this property was critical for estimation of glottal model parameters using phase minimization [25,40]. For the work presented in this article, this same property ensures that the impact of the vocal tract filter on the phase features representing the source is minimal.…”
Section: A Simple Representation Of the Amplitudementioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, using PD, it has been shown that this assumption allows to extract glottal source information which is almost independent of the vocal tract filter [40]. Indeed, this property was critical for estimation of glottal model parameters using phase minimization [25,40]. For the work presented in this article, this same property ensures that the impact of the vocal tract filter on the phase features representing the source is minimal.…”
Section: A Simple Representation Of the Amplitudementioning
confidence: 94%
“…Therefore, in this work, |V i ( f )| encompasses the amplitude spectra of both the glottal source and the vocal tract. Nevertheless, using PD, it has been shown that this assumption allows to extract glottal source information which is almost independent of the vocal tract filter [40]. Indeed, this property was critical for estimation of glottal model parameters using phase minimization [25,40].…”
Section: A Simple Representation Of the Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies in the literature have been devoted to the development of improved methods for modelling aspects of the glottal source and excitation characteristics in speech (e.g., Drugman et al, 2009;Degottex et al, 2011;Kane and Gobl, 2011). Many of these aspects contribute significantly to the perception of voice quality.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in [21], the LF model was optimized using a combinatorial search over the entire parameter space consisting of both the glottal parameters and the VT parameters. Degottex et al [22] presented a novel method that minimizes the error in the phase spectrum using a single parameter voice model.…”
mentioning
confidence: 99%